ANALISIS FAKTOR RISIKO TERJADINYA KEJADIAN KURANG ENERGI KRONIK (KEK) PADA IBU HAMIL - Idris, Idris; Lestyani, Lestyani; Ismanilda, Ismanilda; H, Zulkifli (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Abstract: Pregnant women who experience SEZ have a higher risk of complications during pregnancy and childbirth. Based on the initial survey, it is known that Puskesmas Borong is a health center in East Manggarai Regency that has a high incidence of SEZ. The purpose of the study was to analyze the risk factors for the occurrence of chronic energy deficiency (CHD) in pregnant women. The research design used in this study was cross sectional. The study was conducted in the working area of Puskesmas Borong in July 2024. The population was all pregnant women in the working area of Puskesmas Borong, East Manggarai Regency, namely 119 pregnant women. The sample amounted to 56 respondents. The sampling technique used in this study was Simple Random Sampling. Data analysis was done univariate and bivariate. The results showed a relationship between the age of pregnant women (p value: 0.037) and family income (p value: 0.001) to the incidence of SEZ in pregnant women. It is recommended to the Puskesmas to provide counseling in the class of pregnant women and women of childbearing age to prepare for pregnancy or counseling about nutritional needs before pregnancy and during pregnancy, so that pregnant women can prepare properly.Keywords: Pregnant Women, Family Income, Age of Pregnant Women